Synthesis, characterization and structure determination of novel chromium hexacarbonyl derivatives via substitution with various group 15 complex ligands (L) where L = ethylenebis diphenyl-arsine, P-bromophenyl diphenylphosphane, bis (diphenylphosphino) hexane, bis (diphenylphosphino) pentane, and triphenylarsine - Muhammad Azhar , Mohd Yunus (2012)
The objective of the research study is to synthesize novel compounds through substitution process. The carbonyl ligand on chromium complexes is replaced by different ligands in order to produce a novel organometallic monocrystal compound. The crystal is characterized in terms of its structure, physical and chemical properties. Derivatives of chromium carbonyl are prepared by reaction with a number of group 15 complex ligands which have the potential to result in novel organometallic compounds. Five different ligands were used to produce novel organometallic monocrystal compounds namely Ethylenebis diphenyl-arsine,P-bromophenyldiphenylphosphane,Bis(diphenylphosphino)hexane,Bis(diphenylphosphino)pentane, and Triphenylarsine. From these, the substitution reaction using Ethylenebis diphenyl-arsine and Pbromophenyldiphenyiphosphane both resulted in the formation of sticky light pale yellow crystals, and a fine bright yellow crystal respectively. From the monocrystal Xray diffraction analysis, the resulting novel crystal structure is determined as [cis-1,2- bis(diphenylarsinyl)ethane] tetracarbonylchromium with molecular formula Cr(CO)4(C26H24As2) denoted as Al and trans-bis [(4-bromophenyldiphenyl) phosphane] tetracarbonylchromium with molecular formula Cr(CO)4 (P2C36H28Br2 ) denoted as A2. Infrared spectroscopy (IR) and nuclear magnetic resonance (NMR) further compliment the X-ray diffraction results. For the Al novel structure, the Cr atom is octahedrally coordinated by four carbonyl ligands and single bidentate arsenic ligand, which are bonded in a trans position to each other. The compound crystallizes in the orthorhombic system with an average Cr-As bond length of 2.44865A and average Cr-CO bond length of 1.86975A. For the A2 novel structure, the Cr atom is octahedrally coordinated by four carbonyl ligands and two monodentate tertiary phosphine ligand, which are bonded in a cis position to each other. The compound crystallizes in the triclinic system with an average Cr-P bond length of 2.3509A and average Cr-CO bond length of 1.8895A. Melting point test is also used to determine the melting point of both crystals with Al at 185°C and A2 at 182°C.